COLOR DIFFERENCES OF PINE AND EUCALYPT WOODS MEASURED BY MICROFLASH-200® - Krisdianto Krisdianto (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2007)
It is not easy to define color because it refers to psychological response of human. As a result, perception of color achieved by people is relatively different. Wood color plays an important role in timber processing and it is an important consideration in wood identification. Each wood species has specific color and it becomes the species characteristic. Colors in wood are highly variable and unique features. Characteristics of wood color are influenced by extractive materials and moisture contents present on it. A standard of color measurement has been developed and it is called CIE model. The standard was developed to be completely independent of any devices and was based as closely as possible on human observation in color. CIELAB system is one of the simplest and most practical color measurement methods. The system has been used in one of the color measurement devices developed by Data Color International that is Microflash-200®. This research was aimed at translating interpretation of wood color by human eye into mathematical values so that scientific measurement of wood color can be studied. The measured wood color were 10 species of pines and 10 species of eucalypts woods in dry condition. The results showed that the two groups had different average of L*, a* and b* values. The average of L* for pine was 70.77, while eucalypt group made up to 52.40. It means that eucalypt group is darker than pine group. For a* value, pine group mean value is 20.23, whereas eucalypt group touches 19.11. In other words, pine and eucalypt group have an approximately similar redness. The b* value average for pine and eucalypt groups are 43.40 and 29.07, respectively. This value means that pine group is more yellow than eucalypt group.